The continuums of impairment in vascular reactivity across the spectrum of cardiometabolic health: A systematic review and network meta‐analysis. (18th March 2019) - Loader, Jordan; Khouri, Charles; Taylor, Frances; Stewart, Simon; Lorenzen, Christian; Cracowski, Jean‐Luc; Walther, Guillaume; Roustit, Matthieu
Summary: This study aimed to assess, for the first time, the change in vascular reactivity across the full spectrum of cardiometabolic health. Systematic searches were conducted in MEDLINE and EMBASE databases from their inception to March 13, 2017, including studies that assessed basal vascular reactivity in two or more of the following health groups (aged ≥18 years old): healthy, overweight, obesity, impaired glucose tolerance, metabolic syndrome, or type 2 diabetes with or without complications. Direct and indirect comparisons of vascular reactivity were combined using a network meta‐analysis. Comparing data from 193 articles (7226 healthy subjects and 19344 patients), the network meta‐analyses revealed a progressive impairment in vascular reactivity (flow‐mediated dilation data) from the clinical onset of an overweight status (−0.41%, 95% CI, −0.98 to 0.15) through to the development of vascular complications in those with type 2 diabetes (−4.26%, 95% CI, −4.97 to −3.54). Meta‐regressions revealed that for every 1 mmol/l increase in fasting blood glucose concentration, flow‐mediated dilation decreased by 0.52%. Acknowledging that the time course of disease may vary between patients, this study demonstrates multiple continuums of vascular dysfunction where the severity of impairment in vascular reactivity progressively increases throughout the pathogenesis of obesity and/or insulin resistance, providing information that is important to enhancing the timing and effectiveness of strategies that aim to improve cardiovascular outcomes.